2020
DOI: 10.1007/s10021-020-00497-5
|View full text |Cite
|
Sign up to set email alerts
|

Biocrusts Modulate Responses of Nitrous Oxide and Methane Soil Fluxes to Simulated Climate Change in a Mediterranean Dryland

Abstract: Little is known about the role of biocrusts in regulating the responses of N 2 O and CH 4 fluxes to climate change in drylands. Here, we aim to help filling this knowledge gap by using an eight-year field experiment in central Spain where temperature and rainfall are being manipulated (~1.9 °C warming, 33% rainfall reduction, and their combination) in areas with and without well-developed biocrust communities. Areas with initial high cover of well-developed biocrusts showed lower N 2 O emissions, enhanced CH 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…While we measured N 2 O efflux from each of the three biocrust treatments, the fluxes were extremely small and, with the exception of moss-lichen biocrusts, not statistically different from blanks or control treatments: fluxes averaged around 0.003 nmol m –2 s –1 for all treatments. Lafuente et al (2020) measured somewhat larger biocrust N 2 O fluxes (mean values up to 0.005 nmol m –2 s –1 ) in a field experiment conducted in a Mediterranean dryland, but noted high temporal variability across measurements. They also observed that climatic manipulations (warming and rainfall exclusion) tended to reduce N 2 O fluxes (relative to controls) in some seasons and increase N 2 O fluxes in other seasons.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…While we measured N 2 O efflux from each of the three biocrust treatments, the fluxes were extremely small and, with the exception of moss-lichen biocrusts, not statistically different from blanks or control treatments: fluxes averaged around 0.003 nmol m –2 s –1 for all treatments. Lafuente et al (2020) measured somewhat larger biocrust N 2 O fluxes (mean values up to 0.005 nmol m –2 s –1 ) in a field experiment conducted in a Mediterranean dryland, but noted high temporal variability across measurements. They also observed that climatic manipulations (warming and rainfall exclusion) tended to reduce N 2 O fluxes (relative to controls) in some seasons and increase N 2 O fluxes in other seasons.…”
Section: Discussionmentioning
confidence: 88%
“…Most studies point to CH 4 consumption (methanotrophy) by dryland soils, but there is some evidence of the potential for CH 4 production (methanogenesis) to occur under the right conditions. Lafuente et al (2020) measured CH 4 consumption of up to 1.45 nmol m –2 s –1 by biocrust-covered soils in a semiarid Mediterranean dryland. Durán et al (2021) measured CH 4 uptake by a range of moss- and lichen-dominated cryptogamic soils in Antarctica, although rates of CH 4 uptake were actually 2–3 × higher in bare soil with no cryptogams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the restoration of biocrusts would take more than 10 years after physical disturbance ( Dojani et al, 2011 ), indicating that physical disturbance is an important factor restricting the development of biocrusts. At large scales, physical disturbance causes the reduction of biocrust coverage, which additionally affects the global soil biogeochemical process ( Steven et al, 2014 ; Ferrenberg et al, 2015 ; Yang et al, 2018 ; Lafuente et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%